Deindustrialization, the Linwood Car Plant and Scotland's Political Divergence from England in the 1960s and 1970s. (20th March 2019) - Phillips, Jim; Wright, Valerie; Tomlinson, Jim
Abstract: Scotland's political divergence from England is a key theme in late twentieth century British history. Typically seen in terms of the post-1979 Thatcher effect, this in fact developed over a longer timeframe, rooted in industrial changes revealed by analysis of the Linwood car plant in Renfrewshire. Conservatism and Unionism was an eminent political force in Scotland in the 1940s and 1950s. But in all general elections from 1959 onwards the vote share of Conservative and Unionist candidates was lower in Scotland than in England. From the late 1960s onwards there were also ambitions for constitutional change. This article breaks new conceptual and empirical ground by relating these important markers of political divergence to popular understanding among Scottish workers of deindustrialization. A Thompsonian moral economy framework is deployed. Expectations were elevated by industrial restructuring from the 1950s, with workers exchanging jobs in the staples for a better future in assembly goods. Labour governments earned a reputation in Scotland as better managers of this process than Conservative governments. The 1979 general election showed that Labourism was growing in popularity in Scotland just as its appeal faded in England. At Linwood moral economy expectations were compromised, chiefly by intermittent redundancy and recurrent threat of closure, which was averted in 1975 by Labour government intervention. When the plant was shut in 1981 criticisms of UK political-constitutional structures and Conservativism were intensified.